Avaliação do efeito das infusões de fator VIII sobre biomarcadores imunológicos em crianças com hemofilia A - Larissa Maira Moura de Oliveira (2019)
Hemophilia A (HA) is an inherited bleeding disorder caused by factor (F)VIII deficiency. Its treatment is based on the replacement of deficient FVIII either prophylactically or on demand. One of the major complications of HA is the development of alloantibodies that inhibit FVIII activity (inhibitors). Recent studies suggest that treatment with repeated infusions of FVIII concentrate may alter the immune response and, therefore, contributes to inhibitor development. The objective of this study was to investigate the effect of infusions of FVIII concentrate on immunological biomarkers of patients with congenital HA (PHA). Most (80.3%) PHA were included at diagnosis and before any FVIII infusion (PUPS; previously untreated patients). Socio-demographic, clinical and laboratory variables were collected. Plasma samples were collected at enrollment (T0) and every 5-10 exposure days (ED) to FVIII until at least 75 ED (T1/INB-) or inhibitor development (T1/INB+). Anti-FVIII antibodies (IgM, IgG1, IgG3 and IgG4) were tested by ELISA as well as a panel of chemokines (CCL2, CCL5, CXCL8, CXCL9 and CXCL10) and cytokines (IL-2, IL-4, IL-6, IL-10, INF-, TNF and IL-17A). Descriptive statistical analysis of variables and Spearman correlation between biomarkers were performed. A total of 71 patients with severe (FVIII <1%; n=69) and moderately severe (FVIII 1%-2%; n=2) HA were included. The median age was 10 months (interquartile range [IQR], 6.0-14.0). At T0, there was no difference in the cytokine and chemokine profile between INB- and INB+. The levels of CCL2, CXCL9 and CXCL10 were significantly lower (p=0.02, p=0.0001 and p=0.02, respectively) in the INB+ group when compared with the INB- in the 1-20 ED stratum. Anti-FVIII IgG4 levels in the INB+ group were significantly higher in the strata 1-20 ED (p=0.001) and 21-75 ED (p=0.01) when compared with T0. Anti-FVIII IgG4 in the INB+ group was significantly higher in the 1-20 ED stratum (p=0.01) when compared with INB-. IgG1 showed no significant difference between the two groups nor between the different strata, but there was a trend of increased levels in the INB+ group in the 1-20 DE stratum (p=0.08). We conclude that infusion of FVIII was associated with increased levels of pro-inflammatory cytokines, chemokines, anti-FVIII IgG1 and IgG4 in INB+ patients. These results suggest that FVIII acts by selectively modulating the immune system. Chemokines (CCL2, CXCL9 and CXCL10) are the key elements that differentiate the INB- and INB+ groups during the first exposures to FVIII.